SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK BUAH BUNI (Antidesma bunius (L.) SPRENG) - Arif Rahman; Abd Malik; Aktsar Roskiana Ahmad (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Free radicals play a role in the occurrence of various degenerative diseases that require free-radical scavengers or antioxidants. Buni fruit (Antidesma bunius (L.) Spreng) has the bioactive components are Anthocyanins (flavonoids) that serves to the free radicals. This study aimed to measure the antioxidant activity of theethanol extract contained 70% fruit Buni obtained by using the method of nitric oxide. Simplicia buni macerated dried fruit with 70% ethanol. Extracts were obtained in the test antioxidant activity against nitric oxide radicals. The antioxidant activity against free radical absorbance measured by means of UV-Vis spectrophotometry at a wavelength of 546 nm and calcul ated IC50 values. The results shows that the fruit buni has potential as a free radical with IC50 value of 2.28 µg/mL and a comparison of quercetin with IC50 value of 5.88 µg/mL.